The influence of individual characteristics and work discipline on the performance of PT employees Bank Syariah Indonesia Palopo Branch - Adil Adil; Marhani Marhani; Imelda Rosa (Goodwood Publishing, 2025)
Purpose: This study examines and analyzes the effects of individual characteristics and work discipline on employee performance at PT Bank Syariah Indonesia (BSI) Tbk Palopo Branch. Methodology: This study used a quantitative research with a descriptive approach. The population in this study comprised all employees working at PT. Bank Syariah Indonesia(BSI) Tbk Palopo Branch. Thirty-five samples were used in this study amounted to 35 people. The data analysis techniques used were descriptive statistical tests, classical assumption tests, and multiple regression analysis. Results: The findings reveal that (1) individual characteristics have a positive and significant effect on employee performance; (2) work discipline has a positive and significant effect on employee performance; and (3) both variables simultaneously have a positive and significant effect, contributing 43.20% to performance, while the remaining 56.80% is influenced by other factors not examined in this study. Conclusions: Employee performance in Islamic banking can be enhanced by strengthening both individual characteristics and work discipline. Limitations: This study was limited to a single branch with a relatively small sample size, which reduced the generalizability of the results. Only two independent variables were examined, leaving other potential determinants of performance unexamined. Contribution: This study provides valuable insights into the factors influencing employee performance in the Indonesian banking sector, specifically in the context of Islamic banking. Savings products, especially for BMTs which are still relatively small.